Recipient Toll-like receptors contribute to chronic graft dysfunction by both MyD88- and TRIF-dependent signaling - Wang, Shijun; Schmaderer, Christoph; Kiss, Eva; Schmidt, Claudia; Bonrouhi, Mahnaz; Porubský, Štefan; Gretz, Norbert; Schäfer, Liliana; Kirschning, Carsten Jürgen; Popovic, Zoran V.; Gröne, Hermann-Josef (Disease models & mechanisms, 2010)
Toll-like receptors (TLRs) recognize specific molecular patterns derived from microbial components (exogenous ligands) or stressed cells (endogenous ligands). Stimulation of these receptors leads to a pronounced inflammatory response in a variety of acute animal models. Chronic allograft dysfunction (CAD) was regarded as a candidate disease to test whether TLRs influence chronic fibrosing inflammation....